UNIT 7B.3 Lyophilization of Bdellovibrio bacteriovorus 109J for Long‐Term Storage. Issue 1 (16th May 2017) - Boileau, Mélanie J.; Mani, Rinosh; Clinkenbeard, Kenneth D.
Abstract : Bdellovibrio bacteriovorus 109J is a Gram‐negative predatory bacterium with obligate host dependency on other Gram‐negative bacteria. This bacteriolytic predator collides with, enters, and establishes growth within the prey (host) periplasm, eventually lysing the prey cell wall to release fresh, motile B. bacteriovorus progeny. Laboratory maintenance of B. bacteriovorus has been previously described by other investigators. The protocols included in this unit deal with the technique required to lyophilize or freeze dry host‐dependent B. bacteriovorus . This is an alternative means to frozen glycerol stocks for the long‐term storage of B. bacteriovorus . It includes the cultivation process and methods to lyophilize B. bacteriovorus as well as recommended storage conditions. In addition, this unit provides insight on the formulation's shelf‐life including the time to active culture after reviving lyophilized stocks of B. bacteriovorus following short‐, medium‐, and long‐term storage. © 2017 by John Wiley & Sons, Inc.